Sowing date in five soybean cultivars. I. Effect in the agronomic traits - Motta, Ivo de Sá (2008)
This present work had the objective to evaluate the influence of sowing dates in the agronomic traits of five soybean cultivars, Glycine max (L.) Merril (Leguminosae-Faboideae), in the area of Maringá - PR. For that, were conducted five cultivars assay in the agricultural year of 1999/00, in randomized blocks design. Each assay was sowed in different dates (15/10, 30/10, 15/11, 30/11 and 15/12) and the utilizated cultivars were: BRS 132, BRS 133, BRS 134, BR 16 and FT-Estrela. During the crop developing the evaluated agronomic traits were the number of days for flowering and maturation, the plant height, the degree of the plants layering and the seed yield. The obtained results allowed to conclude that the sowing date presented influence on the number of days for flowering and maturation, reducing the culture cycle with the delay in the sowing. The smallest values of height and degree of plants layering were coincident and occurred in November 22. The BRS 132, BRS 133 and BRS 134 cultivars presented superior crop yield than BR 16 and FT-Estrela. For the crop yield the better sowing date occurred in 15/10